Menciptakan Value Added bagi Ekonomi Lokal dalam Tinjauan Model Rantai Blok dan Konsep Rantai Nilai: Sebuah studi literatur - Heppi Syofya (Journal on Education, 2024)
The emergence of blockchain technology has provided new opportunities to create added value in the local economy. This research conducts a comprehensive literature study on blockchain models and value chain concepts to understand their potential contribution in improving the local economy. This research explores various theoretical frameworks, empirical evidence, and practical applications of blockchain technology and value chain analysis. By synthesizing existing knowledge, this research provides insight into how blockchain and value chain approaches can be leveraged to generate economic value at the local level. These findings contribute to a deeper understanding of the mechanisms by which blockchain technology and the value chain concept can drive economic growth and development in local communities.